2021
DOI: 10.1111/1748-8583.12341
|View full text |Cite
|
Sign up to set email alerts
|

Studying mutuality and perversity in the impacts of human resource management on societal well‐being: Advancing a pluralist agenda

Abstract: Situated within a societal perspective on human resource management (HRM), this paper asks how HRM academics can make a better contribution to understanding the impacts of HRM on societal well-being. It argues that we should target the 'so what?' questions that matter to society, including important issues of employer-employee misalignment and of perverse alignment ('perverseperformance work systems'). It calls for an approach to societal issues in HRM that is problem-focused and theoryinformed. While recognis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 76 publications
(83 reference statements)
2
28
0
Order By: Relevance
“…As Eurofound's (2020, 4) research suggests, workers and societies have much to gain from exploring the opportunities for greater involvement among those in lessskilled occupations, such as 'service and sales workers, machine operators and workers in elementary occupations'. The challenge is to do so in ways that employees and firms find mutually advantageous or that are 'Pareto optimal': benefiting one party without harming the other, and thus, bringing gains to society (Boxall 2021;Freeman and Kleiner 2006).…”
Section: The Sociopolitical Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…As Eurofound's (2020, 4) research suggests, workers and societies have much to gain from exploring the opportunities for greater involvement among those in lessskilled occupations, such as 'service and sales workers, machine operators and workers in elementary occupations'. The challenge is to do so in ways that employees and firms find mutually advantageous or that are 'Pareto optimal': benefiting one party without harming the other, and thus, bringing gains to society (Boxall 2021;Freeman and Kleiner 2006).…”
Section: The Sociopolitical Contextmentioning
confidence: 99%
“…The theory, then, leads to a final point: there is generally a win-win argument in HIWS models (e.g. Boxall 2021;Wood and Ogbonnaya 2018). HIWSs are seen to have the potential to enhance organisational performance through stronger forms of human and social capital and to bring about closer alignment with employee interests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess which antecedents are predictive of the resulting profiles, we conducted a multinomial regression analysis using the package Nnet (v.7. [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This analysis compared the likelihood of an employee being a member of a certain profile with a referent group based on a specific antecedent.…”
Section: Analysesmentioning
confidence: 99%
“…In this context, management and employees are two important internal organizational stakeholders. While the managerial perspective remains dominant in the field of strategic human resource management (SHRM), there have been recent calls to more closely consider the concerns of multiple stakeholders [2] (p. 31) by exploring how win-win situations that directly both benefit employees and management can be achieved [3][4][5]. Empirical studies have demonstrated that high happiness well-being (e.g., employees' satisfaction with their work) and performance can go handin-hand [6,7].…”
Section: Introductionmentioning
confidence: 99%